The sum of \[({1^2} - 1 + 1)(1!) + ({2^2} - 2 + 1)(2!) + ... + ({n^2} - n + 1)(n!)\] is
A. \[(n + 2)!\]
B. \[(n - 1)\left( {(n + 1)!} \right) + 1\]
C. \[(n + 2)! - 1\]
D. \[n\left( {(n + 1)!} \right) - 1\]
Answer
Verified
442.8k+ views
Hint: Here in this question first we will write the given equation in the general form of a variable. The general form of an equation is the form in which when we put the value of the integers, we will get back our basic equation. Then we will simplify the equation to get the final answer.
Complete Complete Step by Step Solution:
The given equation is \[({1^2} - 1 + 1)(1!) + ({2^2} - 2 + 1)(2!) + ... + ({n^2} - n + 1)(n!)\]
Let us assume \[S = ({1^2} - 1 + 1)(1!) + ({2^2} - 2 + 1)(2!) + ... + ({n^2} - n + 1)(n!)\].
We can write it in the general form of a variable as \[S = \sum\limits_{r = 1}^n {({r^2} - r + 1)(r!)} \]
Simplifying above equation, we get
\[ \Rightarrow S = \sum\limits_{r = 1}^n {({r^2} - r + 1)(r!)} = \sum\limits_{r = 1}^n {({r^2} - 1 - r + 1 + 1)(r!)} \]
\[ \Rightarrow S = \sum\limits_{r = 1}^n {\left( {({r^2} - 1) - (r - 2)} \right)(r!)} = \sum\limits_{r = 1}^n {\left( {(r - 1)(r + 1) - (r - 2)} \right)(r!)} \]
Now multiplying \[r!\] to the terms we get, we get
\[ \Rightarrow S = \sum\limits_{r = 1}^n {\left( {(r - 1)(r + 1)r! - (r - 2)r!} \right)} = \sum\limits_{r = 1}^n {\left( {(r - 1)(r + 1)r! - (r - 2)r!} \right)} \]
Now expanding the above equation by putting the value of \[r\] as 1, 2, 3 to \[n\], we get
\[ \Rightarrow S = \left[ {(1 - 1)(1 + 1)! - (1 - 2)1!} \right] + .... + \left[ {(n - 1)(n + 1)! - (n - 2)n!} \right]\]
Subtracting the terms, we get
\[ \Rightarrow S = \left[ {(0)(2)! - ( - 1)1!} \right] + \left[ {(1)(3)! - (0)2!} \right] + .... + \left[ {(n - 1)(n + 1)! - (n - 2)n!} \right]\]
Cancelling out the similar terms, we get
\[ \Rightarrow S = - ( - 1) + (n - 1)(n + 1)! = (n - 1)(n + 1)! + 1\]
Hence, \[(n - 1)(n + 1)! + 1\] is the sum of the given equation.
So, option B is the correct option.
Note:
Here, we need to know the way of writing an equation in the general form of a variable with its variable range. Generally, the value of the variable is positive natural numbers or integers.
Factorial of a number is equal to the multiplication or product of all the positive integers smaller than or equal to the number. In addition, factorial of 1 is always equals to 1 and factorial of 0 is equal to 1. The factorial of a number is always positive, it can never be negative and the factorial of a negative number is not defined.
Example of factorial:\[5! = 5 \times 4 \times 3 \times 2 \times 1 = 120\]
Complete Complete Step by Step Solution:
The given equation is \[({1^2} - 1 + 1)(1!) + ({2^2} - 2 + 1)(2!) + ... + ({n^2} - n + 1)(n!)\]
Let us assume \[S = ({1^2} - 1 + 1)(1!) + ({2^2} - 2 + 1)(2!) + ... + ({n^2} - n + 1)(n!)\].
We can write it in the general form of a variable as \[S = \sum\limits_{r = 1}^n {({r^2} - r + 1)(r!)} \]
Simplifying above equation, we get
\[ \Rightarrow S = \sum\limits_{r = 1}^n {({r^2} - r + 1)(r!)} = \sum\limits_{r = 1}^n {({r^2} - 1 - r + 1 + 1)(r!)} \]
\[ \Rightarrow S = \sum\limits_{r = 1}^n {\left( {({r^2} - 1) - (r - 2)} \right)(r!)} = \sum\limits_{r = 1}^n {\left( {(r - 1)(r + 1) - (r - 2)} \right)(r!)} \]
Now multiplying \[r!\] to the terms we get, we get
\[ \Rightarrow S = \sum\limits_{r = 1}^n {\left( {(r - 1)(r + 1)r! - (r - 2)r!} \right)} = \sum\limits_{r = 1}^n {\left( {(r - 1)(r + 1)r! - (r - 2)r!} \right)} \]
Now expanding the above equation by putting the value of \[r\] as 1, 2, 3 to \[n\], we get
\[ \Rightarrow S = \left[ {(1 - 1)(1 + 1)! - (1 - 2)1!} \right] + .... + \left[ {(n - 1)(n + 1)! - (n - 2)n!} \right]\]
Subtracting the terms, we get
\[ \Rightarrow S = \left[ {(0)(2)! - ( - 1)1!} \right] + \left[ {(1)(3)! - (0)2!} \right] + .... + \left[ {(n - 1)(n + 1)! - (n - 2)n!} \right]\]
Cancelling out the similar terms, we get
\[ \Rightarrow S = - ( - 1) + (n - 1)(n + 1)! = (n - 1)(n + 1)! + 1\]
Hence, \[(n - 1)(n + 1)! + 1\] is the sum of the given equation.
So, option B is the correct option.
Note:
Here, we need to know the way of writing an equation in the general form of a variable with its variable range. Generally, the value of the variable is positive natural numbers or integers.
Factorial of a number is equal to the multiplication or product of all the positive integers smaller than or equal to the number. In addition, factorial of 1 is always equals to 1 and factorial of 0 is equal to 1. The factorial of a number is always positive, it can never be negative and the factorial of a negative number is not defined.
Example of factorial:\[5! = 5 \times 4 \times 3 \times 2 \times 1 = 120\]
Recently Updated Pages
Master Class 11 Accountancy: Engaging Questions & Answers for Success
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Trending doubts
10 examples of friction in our daily life
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE
Define least count of vernier callipers How do you class 11 physics CBSE